The structure of adolescent psychopathology: a symptom-level analysis. Issue 5 (1st December 2015) - Carragher, N.; Teesson, M.; Sunderland, M.; Newton, N. C.; Krueger, R. F.; Conrod, P. J.; Barrett, E. L.; Champion, K. E.; Nair, N. K.; Slade, T.
Abstract : Background: Most empirical studies into the covariance structure of psychopathology have been confined to adults. This work is not developmentally informed as the meaning, age-of-onset, persistence and expression of disorders differ across the lifespan. This study investigates the underlying structure of adolescent psychopathology and associations between the psychopathological dimensions and sex and personality risk profiles for substance misuse and mental health problems. Method: This study analyzed data from 2175 adolescents aged 13.3 years. Five dimensional models were tested using confirmatory factor analysis and the external validity was examined using a multiple-indicators multiple-causes model. Results: A modified bifactor model, with three correlated specific factors (internalizing, externalizing, thought disorder) and one general psychopathology factor, provided the best fit to the data. Females reported higher mean levels of internalizing, and males reported higher mean levels of externalizing. No significant sex differences emerged in liability to thought disorder or general psychopathology. Liability to internalizing, externalizing, thought disorder and general psychopathology was characterized by a number of differences in personality profiles. Conclusions: This study is the first to identify a bifactor model including a specific thought disorder factor. The findings highlight the utility of transdiagnostic treatment approaches and the importance of restructuring psychopathology in an empirically based manner.